2022
DOI: 10.1039/d2tc01168a
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating flexible conductive structures by printing techniques and printable conductive materials

Abstract: The flexible electronics attract great attentions with the enhanced flexibility of electronic devices, which could be used as flexible sensor, flexible battery, electronic skin, soft robot and so on. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 193 publications
0
21
0
Order By: Relevance
“…8–11 The advent and improvement of printed electronics have facilitated the manufacture of flexible/stretchable electronics. 12 It is reported that the market for printed electronics has reached ≈7.8 billion US dollars in 2020, and it is expected to rise to ≈20.7 billion US dollars by 2026. 13,14 Printed electronics have attracted great interest in commercialization because of the ability to manufacture large-scale, low-cost electronic devices on a variety of substrates.…”
Section: Introductionmentioning
confidence: 99%
“…8–11 The advent and improvement of printed electronics have facilitated the manufacture of flexible/stretchable electronics. 12 It is reported that the market for printed electronics has reached ≈7.8 billion US dollars in 2020, and it is expected to rise to ≈20.7 billion US dollars by 2026. 13,14 Printed electronics have attracted great interest in commercialization because of the ability to manufacture large-scale, low-cost electronic devices on a variety of substrates.…”
Section: Introductionmentioning
confidence: 99%
“…For traditional manufacturing technology, the cost of a single product gradually decreases with the increase in production quantity. Printing additive manufacturing technology overturns this cost model, making the cost of a single product and the output show an independent relationship, which is a factor to be considered when achieving scalability . In addition, even with their high complexity, additive manufacturing devices usually do not require new molds, making them less costly to manufacture than other technologies such as lithography and electrochemical deposition .…”
Section: Introductionmentioning
confidence: 99%
“…Printing additive manufacturing technology overturns this cost model, making the cost of a single product and the output show an independent relationship, which is a factor to be considered when achieving scalability. 21 In addition, even with their high complexity, additive manufacturing devices usually do not require new molds, making them less costly to manufacture than other technologies such as lithography and electrochemical deposition. 22 Moreover, the flexibility and efficiency of additive manufacturing technology have made it widely used in preparing electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…36 Screen, inkjet, flexographic, and gravure printing are widely used printing techniques for flexible electronics fabrication. 37,38 Recently, inkjet printing has become popular in fabricating flexible electronics for a variety of applications like biosensors, pressure and strain sensors, gas, temperature, and humidity sensors, flexible and wearable OLEDs, flexible and wearable TFTs, flexible and wearable energy storage devices, 39 tactile sensors, 40 field effect transistors based upon 2D materials, 34 etc. In the inkjet printing technique, conductive ink droplets are deposited through a nozzle onto the substrate to form the desired pattern/circuit.…”
Section: Introductionmentioning
confidence: 99%